TECHNOLOGY ADOPTION CHALLENGES AND MARKETING STRATEGIES FOR MSMES IN SURABAYA: A QUALITATIVE STUDY - Adjeng, Monica; Handayani, Yuliasti Ika (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
The specific purpose of this study is that researchers want to see the readiness of the 14 MSMEs in Surabaya facing competition and their readiness for technology adoption, understanding of brands and product attributes. In terms of this technology, both in the use of machines, marketplaces as a means of buying and selling online and the use of social media as a means of promotion. Understanding brand attributes is also an interesting discussion because the brand is the identity of a product which must then be communicated to potential consumers. This research design uses phenomenology and qualitative study. While the sample selection in this study used a purposive sample, by conducting interviews and brief observations before conducting in-depth interviews using a semi-structured model. The ability of MSMEs in entrepreneurship determines business sustainability. In terms of technology mastery and branding. MSMEs have weaknesses in adapting to join e-marketplaces, financial and sales records, and not many have standardized packaging labels. The constraints of MSMEs are technical capabilities in using computers and their features, making financial reports, and simple sales reports. MSMEs are required to make more efforts to update simple managerial skills and have creativity so that their products have advantages and competitiveness.